Local wisdom in environment conservation: A study on a conservation and energy self-sufficient village - Fandi Sudiasmo; Novi Catur Muspita (Faculty of Social and Political Science, Universitas Airlangga, 2020)
Farmer group of Bendrong Hamlet has conducted a series of reforestation activities to cope with landslides and secure the clean water supply to all villages. Although the attempt has run well, many problems have begun to arise, such as people’s land being sold. The buyers are outsiders, thereby deviating from the specified principles of conservation and people’s awareness of conservation activity decreasing. These problems should be solved immediately, recalling Malang Regency is vulnerable to landslide disaster incidence. The research objectives were to reconstruct the conservation conceptualization model and improve the community-based conservation model using a qualitative research method with a case study approach and interactive data analysis technique. The conservation undertaken by people in Bendrong Hamlet divides into two: green and energy conservations. Green conservation conduct through people planting forests with forestry plants and agroforestry plants below it—energy conservation conduct by processing cow manure into biogas as alternative energy. Besides, the conservation activity is intended to be intended for environmental factors and intended as an economic factor obtained from green and energy conservation activities. Social institutions’ participation, legitimacy, and government, private, and community’s participation, either individually or in the group, are essential to the performance of conservation activity as the attempt of conserving natural resource; also, economic activity should be included in the conservation activity to result in an effective and sustainable community conservation activity.